Foreign direct investment and the risk of regime transition in autocracies. Issue 1 (2nd January 2017) - Escribà-Folch, Abel
ABSTRACT: Economic globalization and, in particular, foreign direct investment (FDI) have often been considered to be catalysts for economic reform and political liberalization. It is argued that openness to foreign investment spurs democratization by empowering pro-liberalization actors and undermining elite cohesion. This article explores and tests three alternative hypotheses linking FDI and autocratic regime survival. The liberalization hypothesis claims that FDI promotes democratization. The state-capture hypothesis suggests that FDI, by increasing the value of power, may raise the risk of an autocratic transition. Lastly, the stabilization hypothesis, contrary to the first two, claims that FDI can enhance dictatorships' stability by opening new opportunities for distributing benefits to regime elites. The empirical analysis, covering about 100 countries for the time period 1970–2008, uses data on autocratic breakdowns and transition types to test the above hypotheses. The reported evidence does not support the liberalization or the state-capture hypothesis. FDI is found to reduce the likelihood of democratic transitions.